Performance Comparisons of Eigensolutions Algorithms of a Symmetric Tridiagonal Matrix on GPU Accelerators - Astsatryan, Hrachya V.; Gichunts, Edita E. (Mathematical Problems of Computer Science, 2021)
While finding the solutions of Hermitian matrix eigenproblem it is a key issue to find an efficient version of algorithms of symmetric tridiagonal solutions. In this paper these algorithms are compared for complex Hermitian matrices in hybrid systems. The methods were carried out on the Tesla C1060 and Tesla K40 GPU accelerators and the performances are presented as between the methods, as well as between the accelerators.